Standard-Dose Proton Pump Inhibitors in the Initial Non-eradication Treatment of Duodenal Ulcer: Systematic Review, Network Meta-Analysis, and Cost-Effectiveness Analysis - Zhang, Jiaxing; Ge, Long; Hill, Matt; Liang, Yi; Xie, Juan; Cui, Dejun; Li, Xiaosi; Zheng, Wenyi; He, Rui (Frontiers in Pharmacology, 2019)
Background: Short-term use of standard-dose proton pump inhibitors (PPIs) is the first-line initial non-eradication treatment for duodenal ulcer (DU), but the choice on individual PPI drug is still controversial. The purpose of this study is to compare the efficacy, safety, and cost-effectiveness of standard-dose PPI medications in the initial non-eradication treatment of DU. Methods: We searched PubMed, Embase, Cochrane Library, Clinicaltrials.gov, China National Knowledge Infrastructure, VIP database, and the Wanfang database from their earliest records to September 2017. Randomized controlled trials (RCTs) evaluating omeprazole (20 mg/day), pantoprazole (40 mg/day), lansoprazole (30 mg/day), rabeprazole (20 mg/day), ilaprazole (10 mg/day), ranitidine (300 mg/day), famotidine (40 mg/day), or placebo for DU were included. The outcomes were 4-week ulcer healing rate (4-UHR) and the incidence of adverse events (AEs). A network meta-analysis (NMA) using a Bayesian random effects model was conducted, and a cost-effectiveness analysis using a decision tree was performed from the payer’s perspective over 1 year. Results: A total of 62 RCTs involving 10,339 participants (eight interventions) were included. The NMA showed that all the PPIs significantly increased the 4-UHR compared to H2 receptor antagonists (H2RA) and placebo, while there was no significant difference for 4-UHR among PPIs. As to the incidence of AEs, no significant difference was observed among PPIs, H2RA, and placebo during 4-week follow-up. Based on the costs of both PPIs and management of AEs in China, the incremental cost-effectiveness ratio per quality-adjusted life year (in US dollars) for pantoprazole, lansoprazole, rabeprazole, and ilaprazole compared to omeprazole corresponded to $5134.67, $17801.67, $25488.31, and $44572.22, respectively. Conclusion: Although the efficacy and tolerance of different PPIs are similar in the initial non-eradication treatment of DU, pantoprazole (40 mg/day) seems to be the most cost-effective option in China.